Classroom Action Research: An Analysis of the Implementation of the Insani Method in Elementary Schools - Zulmasri, Zulmasri; Muhammad Kabil Ikbal; Ardi Satrial; Norman Haziq Bin Salahudin (al-Afkar, Journal For Islamic Studies, 2025)
Learning methods play a role in creating an effective and efficient learning environment that supports the achievement of optimal learning outcomes. Among the methods that can improve the ability to read the Quran is the insani method. The purpose of this study is to analyze the use of the insani method in teaching the Quran to elementary school students. This research uses a Classroom Action Research approach with participant type. The research location was an elementary school in Solok Regency, Indonesia. The informants of this study consisted of teachers and 16 elementary school students. Data collection techniques used observation, and tests. The data analysis technique uses a reduction composed of four steps, namely the planning stage, the implementation stage, the observation, and the reflection stage. The presentation of data in the form of narratives, tables, and histograms. Conclusions were obtained from interpreting data obtained from test results and observations. The insani method is proven to be able to improve student learning outcomes in reading the Quran fluently and mastering tajweed in elementary school students. This can be seen from the achievement of learner learning outcomes that increased from the first cycle of 37% of students who were complete to 88% in cycle II. This achievement has implications for the choice of teacher methods in teaching the Quran to students in elementary schools, especially in learning Islamic Religious Education.